2012
DOI: 10.1371/journal.pone.0043745
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and Pregnancy-Associated ß-Cell Proliferation in Mice Deficient in Proglucagon-Derived Peptides

Abstract: Proglucagon, which is encoded by the glucagon gene (Gcg), is the precursor of several peptide hormones, including glucagon and glucagon-like peptide 1 (GLP-1). Whereas glucagon stimulates hepatic glycogenolysis and gluconeogenesis, GLP-1 stimulates insulin secretion to lower blood glucose and also supports ß-cell proliferation and protection from apoptotic stimuli. Pregnancy is a strong inducer of change in islet function, however the roles of proglucagon-derived peptides in pregnancy are only partially unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
(45 reference statements)
2
8
0
Order By: Relevance
“…Interestingly, phospho-mTOR/mTOR was upregulated, consistent with the hypertrophic phenotype of late gestation (Figure 3A and ONLINE FIGURE IIA). Circulating insulin levels, as reported previously 18, 19 , were elevated in late pregnancy (Online Figure IID). …”
Section: Resultssupporting
confidence: 85%
“…Interestingly, phospho-mTOR/mTOR was upregulated, consistent with the hypertrophic phenotype of late gestation (Figure 3A and ONLINE FIGURE IIA). Circulating insulin levels, as reported previously 18, 19 , were elevated in late pregnancy (Online Figure IID). …”
Section: Resultssupporting
confidence: 85%
“…In contrast, the involvement of gut hormones which normally play a key role in the regulation of beta cell function and survival has been largely overlooked. Interestingly, Sugiyama et al observed that beta cell proliferation was not affected in pregnant glucagon-GFP knock-in (Gcg gfp /Gcg gfp ) mice lacking global proglucagon derived peptides, including glucagon, GLP-1, GLP-2 and oxyntomodulin [48] . However, recent studies have shown that these mice display important compensatory changes even in the non-pregnant state, including markedly increased circulating GIP with substantial ectopic expression of GIP in islet beta cells [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Factors responsible for this are poorly understood but have been suggested to include prolactin, placental lactogens, progesterone and oestrogen [19] . Interestingly, it has recently been shown that proglucagon-derived peptides, such as glucagon-like peptide-1 (GLP-1), are not required for pregnancy-associated beta-cell proliferation [28] . Thus, the present evidence that most alpha-cells co-expressed GIP as well as glucagon is potentially interesting given well established effects of GIP on beta-cell proliferation and survival [20] , [21] .…”
Section: Discussionmentioning
confidence: 99%